BUILDING YOUNG LEARNERS’ CONFIDENCE IN SPEAKING ENGLISH: A Case Study of BELTEI International Schools - By, Dr. Loeung; Veng, Bunthol (Acitya Wisesa: Journal of Multidisciplinary Research, 2024)
Many EFL/ESL teachers in Cambodia still find it challenging to teach English as a foreign language (EFL) or English as a second language (ESL), particularly when working with younger children. The purpose of this study is to determine the potential and problems associated with training young students to speak English confidently.  The study will use a qualitative approach to interview instructors and students about their challenges, primary reasons, and existing methods for helping students practice speaking English. The most important elements affecting early learners’ development are vocabulary and grammar, according to a research conducted with 177 students in levels 1 through 6 and 27 teachers. Motivation, pronunciation, level of difficulty, style of instruction, and fear of making mistakes come next. Teachers nowadays face a wide range of challenges, including shy students, limited L1 competence, mixed-ability classrooms, and poor motivation. Despite these challenges, children enjoy speaking English in their free time. Examples of contemporary teaching strategies include student-active learning, games, conversation, and cooperative learning. Teachers usually provide a comfortable learning environment, encourage conversation among students, and provide clear instructions. However, cooperative learning is not widely used. Students say that using bilingual dictionaries, speaking in class, and answering questions after reading are all great methods to learn. Teachers must reduce students’ anxiety and inspire them more.